2019
DOI: 10.1289/ehp5133
|View full text |Cite|
|
Sign up to set email alerts
|

Identifying and Prioritizing Chemicals with Uncertain Burden of Exposure: Opportunities for Biomonitoring and Health-Related Research

Abstract: BACKGROUND: The National Institutes of Health's Environmental influences on Child Health Outcomes (ECHO) initiative aims to understand the impact of environmental factors on childhood disease. Over 40,000 chemicals are approved for commercial use. The challenge is to prioritize chemicals for biomonitoring that may present health risk concerns. OBJECTIVES: Our aim was to prioritize chemicals that may elicit child health effects of interest to ECHO but that have not been biomonitored nationwide and to identify g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 71 publications
2
59
0
Order By: Relevance
“…To characterize chemicals in environmental media to understand sources of exposures, we extracted results from cohort or probability-based population studies that included children, were conducted primarily in the US, and reported levels in ambient air [ 27 49 ], personal air [ 27 , 28 , 30 34 , 37 , 42 , 43 , 46 , 50 – 55 ], indoor air [ 27 , 29 31 , 33 , 34 , 37 , 39 , 41 , 42 , 45 , 46 , 49 , 56 66 ], house dust [ 29 , 41 , 61 , 62 , 64 , 67 97 ], drinking water [ 97 – 108 ], or food [ 97 , 104 , 108 – 115 ]. For each chemical, we recorded the highest median, mean, or geometric mean values across multiple studies that were detectable in ≥20% of samples (for food, the highest detection frequency for a commodity was selected) [ 26 ]. For chemicals that were detected in ≥20% of samples of one medium and monitored but not detected in another medium, we also display the non-detects.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…To characterize chemicals in environmental media to understand sources of exposures, we extracted results from cohort or probability-based population studies that included children, were conducted primarily in the US, and reported levels in ambient air [ 27 49 ], personal air [ 27 , 28 , 30 34 , 37 , 42 , 43 , 46 , 50 – 55 ], indoor air [ 27 , 29 31 , 33 , 34 , 37 , 39 , 41 , 42 , 45 , 46 , 49 , 56 66 ], house dust [ 29 , 41 , 61 , 62 , 64 , 67 97 ], drinking water [ 97 – 108 ], or food [ 97 , 104 , 108 – 115 ]. For each chemical, we recorded the highest median, mean, or geometric mean values across multiple studies that were detectable in ≥20% of samples (for food, the highest detection frequency for a commodity was selected) [ 26 ]. For chemicals that were detected in ≥20% of samples of one medium and monitored but not detected in another medium, we also display the non-detects.…”
Section: Methodsmentioning
confidence: 99%
“…We indicate the parent compound as well as the relevant metabolite(s) where applicable. To describe concentrations, we recorded the highest 75 th percentile value that was found at any of the NHANES reporting cycles [ 26 ]. To describe linear trends over time, we calculated cycle-to- cycle percentage changes in geometric mean concentrations of biomarkers detected in adolescents during at least three consecutive cycles.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since human tissues are generally not easily accessible for the analysis of POP concentrations, blood is often used as sample matrix for the investigation of human exposure [8]. As exposure of humans to POPs has decreased due to restrictions in the last decades, biomonitoring studies are now focusing on other bioaccumulative compounds like flame retardants, plasticizers, environmental phenols, or fungicides [9]. These compounds are not as persistent as POPs and hence have lower bioaccumulation factors, but the elimination from specimens can still require weeks up to months [9].…”
Section: Introductionmentioning
confidence: 99%